AN ANALYSIS OF STUDENTS’ PRONUNCIATION DIFFICULTIES IN ENGLISH WORDS THROUGH TONGUE TWISTER ACTIVITIES AMONG THE ELEVENTH-GRADE STUDENTS OF SMAS NASRANI 2 MEDAN - Susi Santrika Sitinjak; Carolina Pakpahan; Lastri Wahyuni Manurung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students’ pronunciation difficulties in English words through tongue twister activities among the eleventh-grade students of SMAS Nasrani 2 Medan. The objectives of this research are to identify the types of pronunciation difficulties experienced by students, determine the English phonemes that are most difficult for them to pronounce, and analyze the patterns of pronunciation difficulties that appear in their pronunciation performance. This research applied a descriptive qualitative research design. The participants of this study were 20 eleventh-grade students of SMAS Nasrani 2 Medan in the academic year 2024/2025. The data were collected through tongue-twister reading tasks, classroom observations, audio recordings, and interviews. The students’ pronunciation performances were transcribed using the International Phonetic Alphabet (IPA) and analyzed through data reduction, data display, identification and classification of pronunciation difficulties, and interpretation of the findings. The results of the study show that students experience various pronunciation difficulties in both consonant and vowel sounds. The most frequent consonant difficulties were found in the pronunciation of /ʃ/, /θ/, /v/, /r/ in final position, and /z/. Meanwhile, vowel difficulties occurred in the pronunciation of /ʌ/, /æ/, the diphthong /aɪ/, /u/, and /oʊ/. The analysis also revealed three dominant types of pronunciation difficulties, namely substitution, omission, and reduction or simplification. Among these, substitution was the most frequently occurring error, indicating that students often replaced unfamiliar English sounds with similar sounds from their first language. The findings also indicate that first language interference significantly influenced students’ pronunciation performance. In conclusion, the study reveals that tongue twister activities effectively expose students’ pronunciation difficulties and highlight the English phonemes that are most problematic for learners. These findings provide useful insights for English teachers in designing more effective pronunciation teaching strategies and providing focused pronunciation practice for EFL learners.